The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1080/09640568.2022.2057281
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to sustainable practices in the Indonesian construction industry

Abstract: The adoption of sustainable practices is essential to mitigating negative impacts associated with the global construction industry. This study investigates barriers inhibiting the transition to sustainable practices in the Indonesian construction industry. Using questionnaire as a means of data collection, relevant data was analyzed using reliability and exploratory factor analysis. Based on the analysis, the findings suggest that there were eight underlying factors responsible for the poor awareness of sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Notwithstanding that the lifecycle cost of sustainable buildings has been proven to be cheaper (Tunji-Olayeni et al, 2018), the initial cost and efforts remains a major barrier to its implementation (Fitriani and Ajayi, 2022). Consequently, studies have suggested the need for governments across nations to provide the framework and enablers to facilitate the adoption and implementation of sustainable construction, through policies and legislation (Darko et al, 2017), and by establishing the minimum acceptable standards of sustainability (Ong et al, 2009).…”
Section: Enhancing Sustainability In Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding that the lifecycle cost of sustainable buildings has been proven to be cheaper (Tunji-Olayeni et al, 2018), the initial cost and efforts remains a major barrier to its implementation (Fitriani and Ajayi, 2022). Consequently, studies have suggested the need for governments across nations to provide the framework and enablers to facilitate the adoption and implementation of sustainable construction, through policies and legislation (Darko et al, 2017), and by establishing the minimum acceptable standards of sustainability (Ong et al, 2009).…”
Section: Enhancing Sustainability In Constructionmentioning
confidence: 99%
“…Climate literacy and sustainability have become integrated into construction and general education in many developed nations. However, many developing nations, including Indonesia, are still lacking sustainability education, which is found to be a major barrier to sustainable construction practices (Fitriani and Ajayi, 2022). To address this anomaly, Davies et al (2017) suggest the need to introduce sustainable construction in universities.…”
Section: Enhancing Sustainability In Constructionmentioning
confidence: 99%
“…Here, in Pakistan, due to lack of proper training and counselling of project managers, they do not have enough knowledge and skills required to make their construction projects sustainable and eco-friendly (Hussain et al, 2019). Also, it is observed that project managers do not put conscious efforts and usually don't take the initiative to increase their knowledge in this regard (Fitriani & Ajayi, 2022). This is indeed a major drawback and therefore this critical risk stands at 5 th position in this study, in terms of their probability of occurrence.…”
Section: Risk Assessment Based On Their Probability Of Occurrencementioning
confidence: 99%
“…Additionally, the macro-environment is broader and is made up of external variables (such as natural and physical forces, political and legal issues, technology advancements, economic reasons, etc.) that affect all construction companies' activities (Huang et al, 2013;Hearn and Shakya, 2017;Inti and Tandon, 2021;Fitriani and Ajayi, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…measuring the constructs of the conceptual model. Resources, managerial, and regulatory barriers to the implementation of sustainability practices in HRC projects were measured with a 21-item scale adapted from various sources, namelyPitt et al (2009),Serpell et al (2013), Shokri-Ghasabeh and Chileshe (2014),Shang et al (2021), and Fitrian andAjayi (2022). The level of implementation of sustainability practices (i.e., sustainable construction materials, sustainable construction design, modern construction methods, environmental provision and reporting) was measured with a 24-item scale adapted from multiple sources such asTan et al (20211),Armstrong and Davis (2013),Huang et al, (2013),Hearn and Shakya (2018),McGuire and Morrall (2020), andAranda et al (2021).…”
mentioning
confidence: 99%